Miniimplant Supported Full Dentures. Two-years Study. - P. Barták; R. Šmucler (Czech Dental Chamber, 2012)
Aim of study: The authors of this paper studied possibility of increase of total removable dentures retention using intraosseous implants of small diameter (hereinafter mini dental implants). The study conducted by four dentists under the same conditions (due to reduction of interpersonal differences) investigated survival of immediately functioning implants for two years. Results: From June 2003 to January 2010, four dentists treated 80 patients with total removable denture fixed by mini dental implants; all these patients met study criteria. This was a group of patients in which many of them were medically compromised (patients with cancer and patients with uncontrolled diabetes). Ninety-nine mini dental implants were installed to maxilla and 236 mini dental implants were installed to mandible. In total, 335 mini dental implants were installed. In average, 3.72 mini dental implants were installed to each patient. The patients were regularly followed-up and final evaluation was performed after 24 months of follow-up. In the follow-up period, 29 (8.66%) mini dental implants failed in 10 patients. In total, 306 mini dental implants were fully functioning. Total treatment had to be reinitiated or another method ("standard" implants) had to be used in three patients, i.e. treatment failed in 3.75% of patients. Conclusion: Treatment with total removable denture with retention using mini dental implants could be considered long-term provisional solution with high rate of outcome predictability. This procedure can be an alternative to installation of implants with standard diameter. Comparison with trial investigating standard implants is difficult; however standard implants have higher success rate and indication to use mini dental implants is reasonable in patients in whose standard implants are contraindicated (anatomical conditions and impossible augmentation, medically compromised patients, limited time and financial possibilities etc.).